(untitled) (Altre Modernità, 2022)
If, by definition, the performing event could not do without the co-presence in space and time of spectators and actors (Brook 21), history has shown us how profound reflections on the possibility of shifting the fundamental axes of theater have nevertheless come about. The increasingly substantial presence of video within performances, even if filmed in real-time, is one example that has called into question the fundamental concept of hic et nunc. The creation of performances for a single spectator has altered the anthropological binomial community/ritual in addition to the "non-human" entity of the performer, from metal theater to cyborg performance (Schrum). The Royal Shakespeare Company’s new production (2021) Dream will be analyzed to discuss the particular artistic experimentation that has become widespread in the Covid era. This production, which is a technological performance watched by more than 20,000 people worldwide in just three days, brings performance and gaming technology together to explore new ways for the audience, a remote spectator, to experience live theater (Aebischer 21). As live play performances and readings continually crowd virtual platforms, theater is undergoing a radical shift from stage to screen and cyberspace. However, will these new formats survive in the post-pandemic times?